Ethics Without the Sermon (Harvard Business Review Classics) - L. Nash Laura (Harvard Business Press, 2009)
Corporate values and corporate operations have always been dynamically intertwined, but today more than ever the trend toward focusing on the social impact of the corporation is an inescapable reality that must be factored into managerial decision making. Instead of the utopian and sometimes anticapitalistic bias that marks much of applied business philosophy, this article presents a process of ethical inquiry that is immediately accessible to managers and executives. The process begins with 12 basic questions What is needed is a process of ethical inquiry that is immediately comprehensible to a group of executives and not predisposed to the utopian, and sometimes anticapitalistic, bias marking much of the work in applied business philosophy. First step is a set of 12 questions that draw on traditional philosophical frameworks but that avoid the level of abstraction normally associated with formal moral reasoning.